Climate change and rice production: empirical investigation from Malaysia - Afroz, Rafia; Duasa, Jarita; ., Md Muhibbullah (Global Academic Excellence, 2022)
This paper investigates the link between CO2 emissions, average temperature, planted area, fertiliser use, and rice productivity in Malaysia., covering the period from 1980 to 2018. For this purpose, the study employs the Autoregressive Distributed Lag (ARDL) bounds testing approach and Error Correction Model (ECM) to examine the short-run and long-run relationship among the selected variables of this study. The empirical results obtained from the analysis suggest that carbon dioxide (CO2) emissions and temperature have a long-term favourable influence on rice output in Malaysia but a short-term detrimental impact. Finally, the results obtained from several diagnostic and stability tests are robust, stable, and reliable. The finding of this study could be highly significant for adequate policymaking to reduce the impact of climate change in Malaysia.